Pengaruh Konsentrasi Urin Sapi pada Stek Kopi Robusta BP 308 dan BP 358 (Coffea robusta) - Zaenal Arifin, Aang; Zaedan Fitri, Mohammad (JURNAL AGROPLANT, 2021)
Robusta coffee plants are widely cultivated in Indonesia because they are very well suited to the land in Indonesia when viewed in terms of altitude, air temperature, wind and soil types. However, the problem now is that coffee production has declined and is not optimal in meeting export and domestic needs due to low coffee productivity. The purpose of this study was to determine the effect of cow urine in the breeding of BP 358 and BP 308 robusta coffee cuttings and to determine the response of robusta coffee cuttings growth in cow urine administration.This research was conducted at PTPN XII Silo Sanen's plantation, Mulyorejo Village, Silo District, Jember Regency. This study uses a factorial pattern of 2 x 5 in a randomized block design (RBD) with 4 replications. The first factor of concentration (K) consisted of five levels namely K0 = 0 ml, K1 = 2.5 ml, K2 = 5.0 ml, K3 = 7.5 ml, K4 = 10 ml and the second factor was robusta coffee clones (R ) consists of BP 308 (R1) clones and BP 358 (R2) clones. In total there were 10 treatments, each treatment namely K0R1, K1R1, K2R1, K3R1, K4R1 and K0R2, K1R2, K2R2, K3R2, K4R2. The test is carried out by the F-Test with analysis of variance (ANOVA), if it is significantly different (F-count value> F-table), it will be followed by the Duncan test of 5%. Based on ANOVA results that the treatment of Robusta coffee concentrations and clones as well as the combination of both of the coffee cuttings were not significantly different from the number of shoots, number of roots, dry weight of stems and roots, wet weight of stems and roots, but significantly different from shoot length and root length.